Energy economic analysis of photovoltaic–thermal-thermoelectric (PVT-TE) air collectors. (September 2018) - Nazri, Nurul Syakirah; Fudholi, Ahmad; Bakhtyar, Bardia; Yen, Chan Hoy; Ibrahim, Adnan; Ruslan, Mohd Hafidz; Mat, Sohif; Sopian, Kamaruzzaman
Abstract: Photovoltaic–thermal (PVT) collectors can generate electrical and thermal energy simultaneously. The combination of these two technologies can reduce the required space, time installation and use of materials. PVT air collector present increased total efficiency by increasing solar radiation amount. This review presents the concepts and descriptions, as well as previous works conducted on thermoelectric (TE). A theoretical study of PVT-TE air collectors is also performed. Mathematical models are proposed and solved using iterative process based on the matrix inversion method. An improvement in energy yields can be obtained using TE solar collector technology because TE devices increase the energy conversion efficiency of the system. The annual cost (AC) and annual energy gain (AEG) of PVT-TE air collectors are determined. The cost–benefit ratio or AC per AEG (AC/AEG) is presented for different combinations of mass flow rate and number of TE to increase the feasibility of users in selecting the optimal design features that correspond to minimum AC/AEG. Highlights: The concept, descriptions and previous works conducted on thermoelectric (TE) are presented. A theoretical study of PVT-TE air collector is also performed. Mathematical models are proposed and solved using iterative process based on the matrix inversion method. The annual cost (AC) and annual energy gain (AEG) of PVT-TE air collectors are determined. The optimal design features is correspond to minimum AC/AEG.